My Experience as a Teacher of Catholic Religion in Secondary Education and a Level - Escorcia Torreglosa, Liliany Margarita (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
In the following pages you will find a reflection on the role of catholic religion as a subject, as well as the importance of their teachers in educational innovation at a secondary school level. catholic religion teachers make use of new methodologies and design projects integrating both pedagogical and social initiatives. These initiatives are managed by the religion department and are eventually implemented in the rest of the school. Without undermining the value of the subject itself and its curricular contents, these school projects and diverse methodologies have increased the number of students enrolled and has helped them develop the corresponding competencies. I hope that the information presented here might be helpful to know and value the subject of catholic religion as well as its role within education.